FACTORS IN RELATION TO THE SUCCESS OF THAI FEMALE VOLLEYBALL PLAYERS IN THAILAND - Nakong , Trakarn; Ruekpiboon , Prapas; Quanboonchan, Rajanee (Academic Journal of Thailand National Sports University, 2019)
The purposes of this research were to (1) analyze factors relating to the success of female volleyball players in Thailand and (2) create equation for predicting the success of female volleyball players in Thailand. The sample of this quantitative research which was derived from 1139 population through quota and simple random sampling, included 295 provincial representative volleyball female players, 110 regional representative volleyball female players, 45 representative volleyball female players of Thai junior national team, 30 representative volleyball female players of Thai national youth team, and 15 representative volleyball female players of Thai national team. A set of questionnaire with a 0.77 reliability coefficient was used as a tool to collect data. The statistics used in data analysis were frequency, mean, percentage, standard deviation, confirmatory factor analysis and multinomial logistic regression analysis. The research results were as follows: 1) Factors relating to the success of Thai female volleyball players were significant at the highest level in all aspects ranking in the following descending order: leadership, plan and policy, location, materials, training and competition, potential development of sports personnel, and support and welfare, respectively. 2) Equations for predicting the success of Thai female volleyball players were divided into three types: (1 Thai female volleyball players in junior national team level compared with that of the regional level revealed that predicting factors comprising of leadership, plan and policy were the most statistically significant at a 0.05 level. (2) Thai female volleyball players in national youth team level compared with that of the regional level showed that the potential development of sports personnel was the most statistically significant factor at a 0.05 level. (3) Thai female volleyball players in national team level compared with that of the regional level indicated that training and competition was the most statistically significant factor at a 0.05 level.